Modeling the Impact of a Strong X‐Class Solar Flare on the Planetary Ion Composition in Mercury's Magnetosphere. Issue 3 (5th February 2022) - Werner, A. L. E.; Leblanc, F.; Chaufray, J. Y.; Modolo, R.; Aizawa, S.; Hadid, L. Z.; Baskevitch, C.
Abstract: We model the impact of an extreme solar flare on the Mg +, Na +, O + and He + ion density distribution in Mercury's magnetosphere. The Flare Irradiance Spectral Model of the solar irradiance during the X9.3‐class flare on 6 September 2017 is used as input to the time‐dependent Latmos Ionized Exosphere ion density model. We find that the time‐evolution of the planetary ion distribution differs with respect to energy, location and species. There exist two ion energy populations on the dayside that experience different dynamical evolution. The peak ion density in the nightside plasma sheet is delayed by ∼7–8 min compared to the dayside. The maximum Mg + density occurs ∼4 min before He + and O + in the whole magnetosphere. The time delay between different species does not necessarily occur for solar flares that erupt near the apparent solar limb, where the optical depth is large. Plain Language Summary: A solar flare is a sudden outburst on the Sun which releases radiation and energetic particles. The abrupt radiation enhancement can strongly increase the frequency by which neutral atoms in Mercury's thin atmosphere are ionized. We use a model of the flare radiation spectrum and a new ion density model to study how a strong solar flare impacts the distribution of planetary ions in Mercury's magnetosphere. We select the strongest solar flare of solar cycle 24, which occurred on 6 September 2017. We find that the time‐evolution of the ion density varies depending on the planetary ion species, the location inside the magnetosphere, the ion energy and the location of the flare on the Sun with respect to Mercury. The maximum Mg +  density occurs ∼4 min before He + and O + in the whole magnetosphere. This only happens for solar flares which erupt near the center of the solar disk as seen from Mercury. There are two ion populations with different energies on the dayside, and a single ion population on the nightside. For all species, the peak ion density in Mercury's shadow occurs ∼7–8 min after the corresponding peak on the dayside. Key Points: A strong X‐class flare can boost the photoionization rate of Mercury's Mg, O and He exospheres with 40%–80% The dayside magnetosphere contains two ion populations for each species which respond to the flare on different time scales Depending on the flare geometry, there may be a time delay between the maximum Mg +, O + and He +  ion densities in the magnetosphere